Exploring the effect of natural deep eutectic solvents on zein: Structural and functional properties - Adieh Anvar; Mohammad Hossein Azizi; Hassan Ahmadi Gavlighi (Current Research in Food Science)
This study evaluated the effects of chemical modification, including ethanol, acetic acid, and natural deep eutectic solvents (NADES), on the secondary and tertiary structures, hydrophobicity, free amine content, protein-protein interactions, and functional properties of zein. The NADES used included choline chloride: oxalic acid, choline chloride: urea, choline chloride: glycerol, and glucose: citric acid. The results reveal that the NADES system significantly altered zein's structures, as evidenced by Fourier transform infrared spectroscopy, fluorescence, and Ultraviolet–Visible Spectroscopy analysis. Circular dichroism spectroscopy analysis indicated significant conformational change in modified zein, with decreased α-helix and increased random coil content. Notably, the NADES system leads to greater disruption of hydrogen bonds and facilitates the exposure of hydrophobic regions compared to water, ethanol, and acetic acid systems. This resulted in enhanced solubility, surface hydrophobicity, and free amine content in zein, indicating a more significant change in protein structure. In contrast, water and acetic acid solvents maintained more stable disulfide bonds within zein, which correlates with lower solubility and less unfolding. The NADES system promoted interactions between zein and its solvent components, improving emulsifying properties. Water, ethanol, and acetic acid systems had higher solubility in urea, thiourea, and dithiothreitol than the NADES system, revealing disruption of both covalent and noncovalent bonds in zein modified by NADES. Overall, this study highlights the superior ability of the NADES system to modify zein's structure and functionality compared to conventional solvents, suggesting its potential for enhancing protein applications in the industrial production of foods.